SISTEM TUMPANGSARI DAN INTEGRASI TERNAK TERHADAP PERUBAHAN SIFAT FISIK DAN KIMIA TANAH DI TANAH LITOSOL - Suroyo Suroyo; Suntoro Suntoro; Suryono Suryono (Faculty of Agriculture, Universitas Sebelas Maret, 2013)
Title : Intercropping and Livestock Integration System : Changes in Physical and Chemical Properties of Litosol. Study sites located in the village Geneng duwur, District Gemolong, Sragen regency, Central Java with litosol soil type. Study sites are located between 7 º 23'10